Off-clamp robotic partial nephrectomy: Technique and outcome - Lamoshi, Abdulraouf Y. (Urol Ann, 2015)
INTRODUCTION: Robotic partial nephrectomy (RPN) is a technically challenging procedure. Advanced skills are needed to accomplish tumor resection, hemostasis, and renorrhaphy within short ischemia time in RPN. Off-clamp RPN with zero ischemia may decrease the risk of ischemic reperfusion injury to the kidney. However, the off-clamp technique has been associated with an increased risk of blood loss. The purpose of this study was to evaluate the outcome of our modified off-clamp technique utilized in certain RPN cases. PATIENTS AND METHODS: A total of 81 patients underwent RPN between September 2009 and July 2013 for renal masses. We studied a subgroup of patients who underwent off-clamp RPN with zero ischemia time. The off-clamp technique was utilized for exophytic, nonhilar tumors that have a base of 2 cm or less. We developed a novel technique to avoid ischemia reperfusion renal injury while minimizing blood loss in certain cases of RPN. RESULTS: Of the 81 cases of RPN, we reviewed and adopted the off-clamp technique in 34 patients (41.98%). Utilizing off-clamp RPN resulted in an average blood loss of 96.29 ml and 1.56 days (range: 1-3 days) of hospital stay and minimal change in serum creatinine. CONCLUSIONS: Off-clamp RPN is safe and feasible approach to excise certain kidney tumors. It carries the benefits of RPN and prevents ischemia reperfusion renal injury.